PENDAFTARAN TANAH PERTAMA KALI MELALUI PROGRAM LARASITA DI KANTOR PERTANAHAN KOTA BOGOR - Dwi Nanda Ayuningtyas, Aan Tianlajanu, Albi Aria Padmanaba (GEMA, 2015)
To bring services to the community, Badan Pertanahan Nasional Republik Indoonesia (BPN RI) change the paradigm of the implementation of the basic tasks and function BPN RI of developed Larasita Program. This study aims to determine the effectiveness and implementation constrains through the First Land Registry of the Larasita Program in Bogor City Land Office. Implementation of the First Land Registry of the Larasita Program in Bogor City Land Office is not yet effective. It can be seen from the small number of application is a picture of performance that are less productive and innovative program has not kept pace with the purpose of service improvement Larasita in soil to the public. To increase the effectiveness of the implementation of the First Land Registry of the Larasita Program in Bogor City Land Office, need to organized the implementation of Larasita Program to be focused and clear targets and goals, improving coordination with other parties related to the implementations of the Larasita Program, and implementation of dissemination and extension of the Larasita Program and land issues are held on and ongoing bassies.